Identifikasi gaya mengajar guru fisika dan hubungannya dengan minat belajar siswa - Arjumaidah; Sohibun (Karoteh Utama, 2024)
This study aims to identify the teaching styles employed by Physics teachers in high schools across the Rambah District and analyze their relationship with students' interest in learning Physics. Using a simple correlational design, the study involved a sample from four high schools in Rambah District, consisting of 4 Physics teachers and 80 11th-grade science students. The findings indicate that the assertive teaching style, applied by the Physics teachers, has a significant impact on enhancing students' interest in learning. Data revealed that SMA Negeri 1 Rambah had the highest percentage of assertive teaching style application at 84.54%, which was also associated with high student interest in learning. Although variations in the influence of the assertive teaching style were observed across different schools, overall, this teaching style was effective in increasing student engagement and motivation. These findings support the importance of implementing adaptive and assertive teaching styles to improve the quality of learning, especially in challenging subjects like Physics.